Dependability of Computer-Based Systems - Jones, Cliff B. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2000: Anais do XIV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2000.25917, 2000)
This paper sets out a programme of work in the area of dependability. The research is to be pursued under the aegis of a six-year Inter-Disciplinary Research Collaboration funded by the UK Engineering and Physical Sciences Research Council. The research considers computer-based systems which comprise humans as well as hardware and software. The aim here is to indicate how formal methods ideas, coupled with structuring proposals, can help address a problem which clearly also requires social science input.